Poly(Beta-Amino Ester) Nanoparticles Enable Nonviral Delivery of CRISPR-Cas9 Plasmids for Gene Knockout and Gene Deletion - Yuan Rui; Mahita Varanasi; Shanelle Mendes; Hannah M. Yamagata; David R. Wilson; Jordan J. Green (Elsevier, 2020)
The CRISPR-Cas9 system is a powerful gene-editing tool with wide-ranging applications, but the safe and efficient intracellular delivery of CRISPR components remains a challenge. In this study, we utilized biodegradable poly(beta-amino ester) nanoparticles to codeliver plasmid DNA encoding Cas9 and short guide RNA (sgRNA), respectively, to enable gene knockout following a CRISPR-mediated cleavage at one genomic site (1-cut edit), as well as gene deletion following DNA cleavage at two sites flanking a region of interest (2-cut edits). We designed a reporter system that allows for easy evaluation of both types of edits: gene knockout can be assessed by a decrease in near-infrared fluorescent protein (iRFP) fluorescence, whereas deletion of an expression stop cassette turns on a red-enhanced nanolantern fluorescence/luminescence dual reporter. Nanoparticles enabled up to 70% gene knockout due to small indels, as well as 45% gain-of-function expression after a 600-bp deletion edit. The efficiency of 2-cut edits is more sensitive than 1-cut edits to Cas9 and the sgRNA expression level. We demonstrate promising biodegradable nanoparticle formulations for gene editing. Our findings also provide new insights into the screening and transfection requirements for different types of gene edits, which are applicable for designing nonviral delivery systems for the CRISPR-Cas9 platform.